Electrical transport properties of Ca0.9La0.1−xBixMnO3−δ (0 ≤ x ≤ 0.1) thermoelectric materials. (7th December 2015) - Kim, C.M.; Seo, J.W.; Cha, J.S.; Park, K.
Abstract: A series of Ca0.9 La0.1− x Bi x MnO3−δ (0 ≤ x ≤ 0.1) was fabricated by cold compaction and tape casting methods. The microstructural and thermoelectric properties of Ca0.9 La0.1− x Bi x MnO3−δ were studied, with respect to the partial substitution of Bi 3+ for La 3+ . All of the sintered Ca0.9 La0.1− x Bi x MnO3−δ crystallized in the orthorhombic perovskite structure, belonging to the Pnma space group. The substituted Bi 3+ significantly increased grain size and density because it acted as a sintering additive. The electrical conductivities of tape casting-processed Ca0.9 La0.1− x Bi x MnO3−δ were much higher than those of cold compaction-processed Ca0.9 La0.1− x Bi x MnO3−δ . On the other hand, the absolute values of the Seebeck coefficient for tape casting-processed Ca0.9 La0.1− x Bi x MnO3−δ were similar to those of cold compaction-processed Ca0.9 La0.1− x Bi x MnO3−δ . Consequently, tape casting-processed Ca0.9 La0.1− x Bi x MnO3−δ showed a much higher power factor in comparison with cold compaction-processed Ca0.9 La0.1− x Bi x MnO3−δ . The partial substitution of La 3+ by Bi 3+ up to x = 0.05 led to an increase in the power factor. The highest power factor (3.01 × 10 −4 Wm −1 ·K −2 ) was obtained for tape casting-processed Ca0.9 La0.05 Bi0.05 MnO3−δ at 800 °C. Highlights: Ca0.9 La0.1− x Bi x MnO3−δ is fabricated by cold compaction and tape casting methods. The partial substitution of La 3+ by Bi 3+ in Ca0.9 La0.1 MnO3−δ enhances power factor. Tape casting is effective method for fabricating advanced thermoelectric materials.